A Co-MOF nanosheet array as a high-performance electrocatalyst for the oxygen evolution reaction in alkaline electrolytes. Issue 2 (13th December 2017) - Zhang, Xiaoping; Sun, Weidi; Du, Huitong; Kong, Rong-Mei; Qu, Fengli
Abstract : A Co-MOF nanosheet array on Ni foam (Co-MOF/NF) acts as a superior electrocatalyst for the oxygen evolution reaction, needing an overpotential of only 311 mV to drive a geometrical catalytic current density of 50 mA cm −2 in 1.0 M KOH. Abstract : It is highly attractive to develop high-performance non-noble-metal electrocatalysts for water oxidation in alkaline media. In this communication, we report the hydrothermal growth of a Co-MOF nanosheet array on Ni foam (Co-MOF/NF) as a 3D oxygen evolution reaction catalyst in alkaline media. The Co-MOF/NF demonstrates superior activity and needs an overpotential of only 311 mV to drive a geometrical catalytic current density of 50 mA cm −2 in 1.0 M KOH. Notably, this catalyst also demonstrates superior long-term electrochemical durability for at least 105 h, and it achieves a high turnover frequency of 0.18 mol O2 s −1 at an overpotential of 400 mV.